(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The authorship is a basic element of the continental copyright system and thereare a number of laws dealing with their protection and respect for the author and creator of the original work. New technologies give rise to different approaches interms of protection of works in the digital environment. The emergence of so-calledorphan works has become the new object of study, both nationally and internationally,due to the amount of works that can be covered under this unfortunate conceptof “orphan works“.